Validation of the NG-18 equations for thick walled pipelines. (May 2020) - Lyons, C.J.; Race, J.M.; Chang, E.; Cosham, A.; Wetenhall, B.; Barnett, J.
Highlights: Factors MT  and MP in the NG-18 equations are close to the BS 7910 reference stress. The flow stress dependent NG-18 equations can be applied to thick wall pipe with a full-size Cv ≥ 50 J. The flow stress dependent NG-18 equations may be used in a failure frequency model for CO2  pipelines. Abstract: The applicability of the flow stress dependent NG-18 equations to thick wall pipelines such as those used to transport dense phase carbon dioxide (CO2 ) is demonstrated. A comparison between the components of the NG-18 equations and BS 7910 shows that the factor MT for though-wall defects and MP for part-wall defects in the NG-18 equations are very close to the reference stress solutions in BS 7910 Annex P, which are applicable to thick wall pipe. Thus, by inference, the flow stress dependent form of the NG-18 equations is also applicable to thick wall pipe. A further comparison with experimental failure data for thick wall pipes shows that the flow stress dependent NG-18 equations are applicable to wall thicknesses of up to 47.2 mm when the full-size equivalent upper shelf Charpy V-notch impact energy is at least 50 J. The results suggest that in principle, the flow stress dependent NG-18 equations may be used as limit state functions in models to calculate the failure frequency due to third party external interference, for high toughness, thick wall pipelines such as those required for dense phase CO2 pipelines.